Um judeu batista no Brasil: relações entre protestantismo, estado e sociedade no período da Velha República com base na narrativa do missionário batista Salomão Ginsburg - Oliveira, Edson Douglas de (2017)
The purpose of this research is to draw a panel on the history and progress of Protestantism in Brazil from the narrative reconstruction of the life and missionary ministry of Solomon Ginsburg, one of the first Baptist missionaries in activity in Brazil, Who came to the country at the end of the century XIX (1890) and remained in activity for more than thirty years. Ginsburg, a Jew born in Poland in 1867 and converted to Protestantism in England, became a missionary in Brazil where he served for more than thirty years, passing away in São Paulo in 1927 in full exercise of his ministry. In his missionary activity, Ginsburg founded churches, mainly in the states of Rio de Janeiro (Campos region) and Pernambuco, polemicized against the Catholic Church through the press or public debates and influenced the bases of the hymnology of the Baptist church through the hymnal Christian Cantor, edited and published for the first time in 1891 and since then has been the official anthem of that denomination. However, in order to establish the full realization of these actions, Ginsburg had to rely on the networks of relations and power that he gradually built in the country, particularly with political elements, notably those he described as "political chiefs" in the interior of the country, also with high class heroes, professionals, judges, police officers and, above all, from the Masonry of which he was an active member, besides other public agents. Understanding these relationships and how they influenced not only Ginsburg's modus operandi in his missionary work in Brazil, but also the very progress of the Baptist Church in Brazilian lands, and this particular experience was constituted in a panoramic view of the wider process of Insertion of Protestantism within the Brazilian Society at the beginning of the republican period, It is the purpose of this research